Research and Practice on the Influence of Hydropower Station Construction on River Connectivity in the Process of Urbanization - WANG Shenfang; YANG Xiaoling; LIANG Wenshan (Renmin Zhujiang)
River connectivity features longitudinal,lateral,and vertical dimensions,as well as time.Specifically,the longitudinal dimension (longitudinal connectivity) is highly disturbed and widely affected by human activities in the process of urbanization.Based on the research and practice of the longitudinal river connectivity both in China and abroad in terms of concepts,research mechanisms,and calculation methods,this paper took the Nanshan River Basin in Yunfu city,Guangdong Province as an example and adopted the VCI,barrier coefficient,improved barrier coefficient,and DCI methods to quantitatively evaluate the influence of hydropower station construction on longitudinal river connectivity.In addition,by calculating the impact of each hydropower station on the connectivity,the paper proposed suggestions for restoring the river connectivity in a targeted manner,which provides a reference model for the development and construction of water conservancy and hydropower and the management of small and medium-sized river basins.